Emergency department nurses' competences: implementing a personal dossier for nurses onboarding, skills maintenance, and quality audit - Marco Ruggeri; Laura Rasero; Angela Brandi; Stefano Bambi (Firenze University Press, 2023)
Emergency Departments (EDs) are among the most challenging clinical settings for nurses. EDs are complex settings, including patients with various clinical severity levels, every typology of medical and surgical specialties, fast organizational responses, a triage area to identify the clinical priorities to access a medical visitation, and simultaneous emergency codes to be managed. Therefore, the issue of acquiring and maintaining adequate competencies to manage the delivery of nursing care in a multifaceted setting such as ED is central. Orientation and onboarding programs with very different characteristics in terms of content, duration, and delivery methods are present worldwide. These programs can include clinical skills self-assessment, structured learning opportunities, e-learning, development of core skills, portfolios. The possibility of integrating different educational strategies to gain knowledge with time spent in specific clinical areas to increase experience is the winning way to obtain the growth and maintenance of ED nurses' competencies. In this paper, we report on the experience (currently in progress) related to the ongoing performance evaluation of ED nurses' activities during 12 months in the Emergency Department of Careggi University Hospital. In particular, a printed annual "Professional dossier" was designed with two-fold aim. The staff nurse holder of the booklet can handle a realistic summary of his/her activities, case mix, and time spent in the diverse clinical areas of the ED, comparing these data with opportune standards provided to make adequate comparisons and pinpoint the professional improvements that are needed. The nurse coordinator and nurse manager can use nurses' personal dossiers to know the realistic competencies load in the ED, balance the work shifts with adequate skill mix, program the rotation of nurses in the different clinical areas during the year to ease the maintenance of experience and expertise, and have a photograph of some important performance indicators for hospital personnel evaluation.